2020
DOI: 10.1093/aob/mcaa164
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and taxon age are associated with differing patterns of hybridization in twoEucalyptus(Myrtaceae) subgenera

Abstract: Background and Aims Hybridisation is an important evolutionary process that can have a significant impact on natural plant populations. Eucalyptus species are well-known for weak reproductive barriers and extensive hybridisation within subgenera but there is little knowledge of whether patterns of hybridisation differ among subgenera. Here, we examine eucalypts of Westerns Australia’s Stirling Range to investigate how patterns of hybridisation are associated with landscape and taxon age betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In this study, we have used whole-genome resequencing data to identify seven genetically divergent Populus species and to certify that several previously ambiguous species are all hybrids. Owing to the morphological distinct cohort of hybrids, especially for long-lived trees, hybrid individuals can often be recognized and misclassified as separate species, which have been reported in Eucalyptus , Juglans , and Quercus ( Burgarella et al 2009 ; Robins et al 2021 ; Zhang et al 2022 ). We found that except for P. × canescens where a few individuals were found to be backcrossed hybrids, all other previous ambiguous species are all first-generation hybrids between different pairs of distinct species.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have used whole-genome resequencing data to identify seven genetically divergent Populus species and to certify that several previously ambiguous species are all hybrids. Owing to the morphological distinct cohort of hybrids, especially for long-lived trees, hybrid individuals can often be recognized and misclassified as separate species, which have been reported in Eucalyptus , Juglans , and Quercus ( Burgarella et al 2009 ; Robins et al 2021 ; Zhang et al 2022 ). We found that except for P. × canescens where a few individuals were found to be backcrossed hybrids, all other previous ambiguous species are all first-generation hybrids between different pairs of distinct species.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2020), poplar (J. Wang, Street, Scofield, & Ingvarsson, 2016;, Eucalyptus (Robins, Binks, Byrne, & Hopper, 2021), oaks, and mangroves (Burgarella et al, 2009;Fu et al, 2022;Qiu et al, 2008;R. Zhou, Gong, Boufford, Wu, & Shi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Current hybridisation has been observed in many eucalypts (e.g. Field et al 2011;Bradbury et al 2016;Robins et al 2021) and also in species of Corymbia (Shepherd et al 2008;Ochieng et al 2010). Even though hybridisation between C. haematoxylon and C. calophylla, and between C. ficifolia and C. calophylla, has been noted anecdotally in localised situations, we did not seek to test this explicitly and rather sought to determine species-level relationships separate from any localised recent hybridisation.…”
Section: Relationships Among Speciesmentioning
confidence: 99%